Case Report on Right Chronic Dacryocystitis with Lacrimal Sac Abscess (Journal of Pharmaceutical Negative Results, 2022)
Background: Dacryocystitis of the lacrimal sac, can be acute or chronic. Chronic dacryocystitis is prevalent, but acute dacryocystitis is uncommon, and it's usually caused by a nasolacrimal duct obstruction. Traumatic injury, infections, inflammations, and neoplasms are all possible causes of nasolacrimal duct obstruction (NLDO). Whatever causes NLDO, it leads to the stalling of tears, the accumulation of mucoid secretions, and the desquamation of cells, providing an ideal environment for bacterial infections and the development of dacryocystitis. Case presentation: A 23 years old male came to the ENT department with the chief complaint of right eye watery discharge for 1 year, and right lower eyelid swelling with pain over the right side of the face for 1 month. The patient had a history of road traffic accidents one year ago. For that, he underwent open reduction and internal fixation. But after 9 months, he was having a history of right frontozygomatic suture region infected plate for which he underwent surgery of infected Removal with right orbital volume correction. He had a history of 2 units of blood transfusion with no allergic reaction. On arrival, a physical examination of the eye was carried out which shows swelling over the right eyelids along with tenderness. The Contrast Enhanced Computed Tomography of paranasal sinuses was done along with the dacryocystography under local anesthesia after that he has undergone through Dacryocystorhinostomy under general anesthesia and later he was treated with antibiotics, analgesics, and antacids.Conclusion: It is an inflammation of the tear-producing gland. Chronic dacryocystitis has 2 types namely, primary and secondary types. The primary variety, which affects 80% or more of women, is widespread and distinguished by a strong sex preference. The most significant contributing component to its cause appears to be heredity. The prevalence of the second variant is uncommon and roughly equal in both sexes. It is brought on by an illness or injury to the nearby parts. An external dacryocystorhinostomy is the best method of treatment for this condition.